Accuracy of venous thromboembolism assessment and compliance to prophylaxis in a tertiary care center. (September 2016) - Kim, Pamela S; Gasparis, Antonios P; Probeck, Kristan; Elitharp, Doreen; Tassiopoulos, Apostolos; Labropoulos, Nicos
Background: Proper assessment of venous thromboembolism (VTE) risk level in hospitalized patients is vital to providing adequate prophylaxis. Clinical decision support (CDS) tools with electronic medical record (EMR) have been used by institutions to improve assessment and prophylaxis. As such, this study was conducted after implementing such a system to compare admitting service (AS) assessment of VTE risk level to the VTE consult service (CS) assessment. In addition, compliance of ordered prophylaxis based on AS assessment was evaluated. Methods: At a tertiary care center, we performed a review of randomly selected patients assessed within 18 h of admission for VTE risk over a five-month period. A total of 104 patients were evaluated, four of which were excluded because of VTE presence on admission. Patients were assessed for VTE risk independently, first by the AS, followed by the VTE CS. Prophylaxis orders were then reviewed based on AS assessment compliance to CDS recommendations for prophylaxis based on ACCP guidelines. Results: All 100 patients underwent VTE risk assessment within 18 h from admission. The mean age was 63 years. Comparing AS to CS assessment, 13 patients had incorrect assessments ( p < .001). Of these, six patients were under-assessed ( p = .029), and seven patients were over-assessed ( p = .014). Based on AS assessment there were eight patients who had incorrect prophylaxis ordered. Unnecessary exposure to complications due to inappropriate prophylaxis occurred in five patients. Conclusion: Despite the use of EMR CDS tools, there continues to be a significant number of patients that are being under-assessed and under-prophylaxed for VTE resulting in exposing patients to potential harm. Quality programs need to be instituted to further improve VTE assessment and prophylaxis.